PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN PADA KPP MAKASSAR UTARA - Setiawati, Linda; Todingbua, Manuel A.; Halik, Johannes Baptista (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2025)
The aim of this study is to analyze the impact of good corporate governance and tax sanctions on companies' compliance with tax obligations at the North Macassar Tax Office, as there are still compliance issues in various regions. This study uses a quantitative approach with number-based data. The sample consisted of 96 companies selected at random. The results show that the implementation of good corporate governance does not have a significant impact on companies' compliance with tax regulations. In contrast, tax penalties have a significant impact on the level of compliance with tax obligations by companies with the North Makassar Tax Office.